Erratum to: The visual amplification of goal-oriented movements counteracts acquired non-use in hemiparetic stroke patients - Rubio Ballester, Belén; Nirme, Jens; Duarte, Esther; Cuxart, Ampar; Rodriguez, Susana; Verschure, Paul; Duff, Armin (Journal of neuroengineering and rehabilitation, 2015)
Unfortunately, in the original version of this article [1] the sentence "This project was supported through ERC project cDAC (FP7-IDEAS-ERC 341196), EC H2020 project socSMCs (H2020-EU.1.2.2. 641321) and MINECO project SANAR (Gobierno de España)" was missing from the acknowledgements.The acknowledgements have been correctly included in full in this erratum.